The Effect of Scientific Approach Based on Tutorial Video on Students’ Reading Comprehension of Procedure Text (A Quasi-Experimental Research at Grade VIII of SMPN 4 Kota Bengkulu) - Ahyauddin Ma’id; Azwandi Azwandi; Arono Arono (Journal of Applied Linguistics and Literature)
This research aimed to find out whether there was any effect of implementation scientific based approach using tutorial video on students’ reading comprehension as a whole and various aspects in procedure text at grade VIII of SMPN 4 Kota Bengkulu. The design was a quasi-experimental research. The sample consisted of 50 students at grade VIII SMPN 4 Kota Bengkulu, 25 students for experiment group and 25 students for control group. The instrument was a reading test which comprised 50 multiple choice questions, the instrument was tried out with r=0,970. The research findings were as follows; (1) Scientific approach based on tutorial video affected students’ whole reading comprehension; (2) scientific approach based on tutorial video affected students’ reading comprehension in various aspects of reading comprehension, namely; finding general information, finding specific information, integrating information, and learning from text. Further study is recommended for other text types.